Development strategies for flyingfish fisheries of the Eastern Caribbean - Mahon, Robin (IDRC OttawaCA, 1986)
Describes the flyingfish fisheries and identifies problems with their development. Provides review and analysis of the biology and population dynamics of the four wing flyingfish, and attempts to assess their response to exploitation. Outlines and discusses some options and approaches to stock assessment and management.